Analisa Pengaruh Citra Merek Dan Kualitas Pelayanan Terhadap Loyalitas Nasabah Bank BRI Kantor Cabang Muara Teweh - Rusli, Henny Rosgiaty (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2020)
This study aims to determine the effect of partial brand image on customer loyalty BRI Bank Muara Teweh Branch Office. To determine the effect of service quality partially on customer loyalty BRI Bank Muara Teweh Branch Office. To find out the effect of brand image and service quality simultaneously on loyalty customer of BRI Bank Muara Teweh Branch Office. This research method uses In this research the method used is an associative method which is causal that is a study that aims to determine the relationship between two or more variables. The population in this study was 350,706 and the number of samples taken in this study were 100 people. In this study, multiple regression analysis is used to determine the extent of the influence of independent variables on the dependent variable. The data collection results are concluded. There is an influence of brand image on customer loyalty with Positive coefficient means that the more brand image increases, the more customer loyalty increases. There is an influence of service quality on customer loyalty increasing the influence of service quality increases customer loyalty. There is an influence of brand image and service quality together on customer loyalty so that BRI Bank Muara Teweh Branch Office. It is recommended that BRI Bank Muara Teweh Branch Office provide training to employees whose job is to serve customers so that they have the same standards in hospitality, speed in service, and accuracy in responding to customer complaints and improve service quality.